Childhood neurodevelopmental markers and risk of premature mortality: Follow-up to age 60-65 years in the Aberdeen Children of the 1950s study. - Adele Warrilow; Geoff Der; Sally-Ann Cooper; Helen Minnis; Jill P Pell (PLoS ONE, 2021)
Background Individual neurodevelopmental disorders are associated with premature mortality. Little is known about the association between multiple neurodevelopmental markers and premature mortality at a population level. The ESSENCE (Early Symptomatic Syndromes Eliciting Neurodevelopmental Clinical Examinations) approach considers multiple neurodevelopmental parameters, assessing several markers in parallel that cluster, rather than considering individual diagnostic categories in isolation. Objectives To determine whether childhood neurodevelopmental markers, including reduced intellectual functioning, are associated with all-cause premature mortality. Methods and procedures In a general population cohort study (n = 12,150) with longitudinal follow up from childhood to middle age, Cox proportional hazard models were used to study the associations between childhood neurodevelopmental markers (Rutter B scale and IQ) and premature all-cause mortality. Outcomes and results The cognitive measures and 21 of the 26 Rutter B items were significantly associated with premature mortality in bivariate analyses with hazard ratios from 1.24 (95% CI 1.05-1.47) to 2.25 (95% CI 1.78-2.90). In the final adjusted model, neurodevelopmental markers suggestive of several domains including hyperactivity, conduct problems and intellectual impairment were positively associated with premature mortality and improved prediction of premature mortality. Conclusions A wide range of neurodevelopmental markers, including childhood IQ, were found to predict premature mortality in a large general population cohort with longitudinal follow up to 60-65 years of age. Implications These findings highlight the importance of a holistic assessment of children with neurodevelopmental markers that addresses a range of neurodevelopmental conditions. Our findings could open the door to a shift in child public mental health focus, where multiple and/or cumulative markers of neurodevelopmental conditions alert clinicians to the need for early intervention. This could lead to a reduction in the risk of broad health outcomes at a population level.